Seeing in depth - Howard, Ian P.; Rogers, Brian J. (New York ; Oxford : Oxford University Press, 2008)
In its two volumes 'Seeing in Depth' provides a detailed review of all aspects of seeing the three-dimensional world, along with 7,000 references and 800 illustrations. This book is a valuable resource for researchers in space perception, visual neuroscience, opthalmology, optometry, visual development, animal vision, and computational vision.
v.1. Basic mechanisms -- v. 2. Depth perception.
Description based on information supplied on publisher's spreadsheet; title from spreadsheet (viewed on Apr. 13, 2012).
Keywords: Depth perception